Relationship between Hypertension and Aorta Arch Calcification on Chest X-Ray Photos of Ischemic Stroke Patients at The General Hospital Haji Adam Malik Medan 2022 - Muhammad, Mufti; DL, Netty; AB, Chairil (CoinReads Media Prima, 2023)
Introduction: Fatty liver is a broad term for a condition in which there is an increase triglyceride level in hepatocyte. In Indonesia there is not much research about this condition. Fatty liver is a major health problem in West countries, and is slowly increasing in Asian countries. For many individual with fatty liver, have no specific complaint or can have no symptoms at all. The aim of this study was to analyzed the relationship between fatty liver images on abdominal CT scans with dyslipidemia. Method: This study is an observational analytic study with a case – control type of research with the aim of knowing the relationship between CT scan images of fatty liver and dsylipidemia. The data in this study were all medical records who went to the Radiology Department for abdominal CT Scan at the Haji Adam Malik General Hospital for a period of one year from January 1st, 2020 to December 31st 2020. Results: The subjects on the abdominal CT scan results with fatty liver and high triglyceride is 5 peoples out of 12 (41.7%). The test results obtained p value = 0.,688 (p>0,05), in other words there is no significant relationship between fatty liver and high triglyceride level. Conclusion: No significant relationship was found between the incidence of fatty liver and the incidence of dyslipidemia.